HER-2 GENE, RECEPTORS AND DRUG TARGET: A SYSTEMATIC REVIEW - Holla, Sadhana N; Nayak, Veena; Bairy, K Laxminarayan; Tripathy, Amruta; N, Shreedhar Holla (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
The discovery and identification of the human epidermal growth factor receptor 2 (HER's-2) genes, have led to a better understanding of breast tumour biology. A member of the epidermal growth factor receptor family, it is a potent mediator of cellular growth and proliferation in malignant epithelial cells. Amplification or over expression of HER-2 occurs in approximately 15–30 % of breast cancers and 10–30 % of gastric/gastroesophageal cancers and serves as a prognostic and predictive biomarker. Treatment with HER-2 targeted monoclonal antibody, trastuzumab dramatically improved outcome in patients with breast malignancy. This promising approach led to the development of pertuzumab, ado-trastuzumab emtansine and lapatinib. The development of drug resistance and disease progression due to alternate signalling remained a real therapeutic challenge. Several research studies are currently focused on inhibition of onco-proteins, kinases and growth factors linked to HER-2 positive breast cancers. The success of immune checkpoint modulators and vaccines in preliminary studies describes the role of tumour immunity. Apart from its role in the pathogenesis of various cancers, HER-2 directed therapeutic approach has brought about a revolutionary change in terms of time to progression and survival rates in breast cancers. Keywords: ErbB-2 signalling, Targeted approach, Trastuzumab, Drug resistance